(untitled) (Journal of Dhaka Medical College, 2015)
Introduction: The Comminuted trochanteric and subtrochanteric femoral fractures are considered as one of the most difficult fractures to treat in the orthopaedic surgery and they associated with high incidence of nonunion, malunion. Various implants, both intramedullary and extramedullary, are available for their fixation. Objective: To assess the success rate of proximal femoral locking compression plate osteosynthesis in comminuted trochanteric and subtrochanteric femoral fracture in lateral decubitus approach without per operative image intensifier. Method: 20 consecutive patients with comminuted Trochanteric and subtrochanteric fractures were operated upon with PF-LCP. Detailed clinical conditions of all patients, duration of operation, technical difficulty with the implant, hospital stay period were recorded. Patients were visited at 6 weeks interval till union then 3 monthly. The Harris Hip Score was used to document hip function at final follow-up. Result: There were fifteen excellent (75%), two good (10%), two fair (10%) and one poor (5%) results according to Harris hip score. No instance of implant failure was recorded. Conclusion: Fixation of comminuted subtrochanteric fractures with PF-LCP in lateral decubitus approach without per operative image intensifier provides stable fixation with high union rate and fewer complications. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 179-185